2016
DOI: 10.11646/phytotaxa.277.3.7
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Chrysosplenium (Saxifragaceae) from Zhangjiajie, Hunan, central China

Abstract: A new species of Chrysosplenium (Saxifragaceae), C. zhangjiajieense, is described and illustrated from Zhangjiajie, Hunan province in China. This new species is similar to C. macrophyllum in having broad basal leaves and compact cymes, but it differs from the latter in that the whole plant of C. zhangjiajieense is densely covered by coarse and long white villus, and the leaf adaxial surface bears thickly wart points. The new species is also similar to C. davidianum, but differs by having white flowers, only on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 0 publications
1
22
0
Order By: Relevance
“… Macrophylla contains five species including C. chinense (Hara) J.T.Pan, C. davidianum Dence. ex Maxim, C. macrophyllum Oliv., C. glossophyllum Hara and a recently-described species C. zhangjiajieense ( Pan 1986a ; Liu et al 2016 ). Amongst them, the new species is most similar to C. macrophyllum and C. zhangjiajieense by stamens long exserted from sepals, but can be distinguished based on plant height, rhizome, stolon, sterile branch, basal leaf, flower colour and stamen morphology as summarised in Table 1 .…”
Section: Taxonomic Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“… Macrophylla contains five species including C. chinense (Hara) J.T.Pan, C. davidianum Dence. ex Maxim, C. macrophyllum Oliv., C. glossophyllum Hara and a recently-described species C. zhangjiajieense ( Pan 1986a ; Liu et al 2016 ). Amongst them, the new species is most similar to C. macrophyllum and C. zhangjiajieense by stamens long exserted from sepals, but can be distinguished based on plant height, rhizome, stolon, sterile branch, basal leaf, flower colour and stamen morphology as summarised in Table 1 .…”
Section: Taxonomic Treatmentmentioning
confidence: 99%
“… Macrophylla by leaves all alternate, seed minute papillae, ovary semi-inferior and disc absent ( Pan 1986a , b ). A thorough literature survey ( Pan 1992 ; Pan and Ohba 2001 ; Liu et al 2016 ; Kim et al 2019 ) and review of herbarium specimens at A, E, HNWP, HZU, IBSC, KUN, MO, NEFI, NWTC, PE, SI, WUK (herbarium acronyms according to Index Herbariorum; Thiers 2019 ), suggested that it is a distinct and undescribed species.…”
Section: Introductionmentioning
confidence: 99%
“…The genus plays an important role in the phylogeny of Saxifragaceae, comprises about 79 perennial herbs [7], and mainly occurs in the northern hemisphere, with the highest species diversity in East Asia; only two species, Chrysosplenium valdivicum Hook and Chrysosplenium macranthum Hook, are found in the Southern Hemisphere [8,9]. Thirty-six species and fifteen variants have been recorded in China [10,11]. Chrysosplenium is divided into two subgenera according to the leaf arrangement: Alternifolia Franchet with alternate leaves and Oppositifolia Franchet with opposite leaves [8,10,12].…”
Section: Introductionmentioning
confidence: 99%
“…The genus plays an important role in the phylogeny of Saxifragaceae, comprises about 79 perennial herbs [7], and mainly occurs in the northern hemisphere, with the highest species diversity in East Asia; only two species, Chrysospleniumvaldivicum Hook and Chrysospleniummacranthum Hook, are found in the Southern Hemisphere [8,9]. Thirty-six species and fteen variants have been recorded in China [10,11]. Chrysosplenium is divided into two subgenera according to the leaf arrangement: Alternifolia Franchet with alternate leaves and Oppositifolia Franchet with opposite leaves [8,10,12].…”
Section: Introductionmentioning
confidence: 99%